2016
DOI: 10.1016/j.ymgmr.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Divergent clinical outcomes of alpha-glucosidase enzyme replacement therapy in two siblings with infantile-onset Pompe disease treated in the symptomatic or pre-symptomatic state

Abstract: Pompe disease is an autosomal recessive, lysosomal glycogen storage disease caused by acid α-glucosidase deficiency. Infantile-onset Pompe disease (IOPD) is the most severe form and is characterized by cardiomyopathy, respiratory distress, hepatomegaly, and skeletal muscle weakness. Untreated, IOPD generally results in death within the first year of life. Enzyme replacement therapy (ERT) with recombinant human acid alpha glucosidase (rhGAA) has been shown to markedly improve the life expectancy of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…These results, compared to those of CRIM-positive patients who begun therapy at symptoms appearance [ 12 15 ], suggest a positive impact of newborn screening programs for Pompe disease. However, an increasing number of observations have been recently published showing that early pre-symptomatic treatment in CRIM-positive, low antibody titer patients does not completely prevent slow deterioration after the first years of life [ 10 , 31 , 32 ]. Moreover pre-symptomatic treatment does not always guarantee a positive outcome in a short-term, as shown by Schänzer et al [ 33 ], who reported an extreme case of a CRIM-positive, low antibody titer IOPD infant, treated since the 3rd day of life with 40 mg/kg/week who never achieved free sitting position and was tracheostomized and ventilated from 10 months on [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results, compared to those of CRIM-positive patients who begun therapy at symptoms appearance [ 12 15 ], suggest a positive impact of newborn screening programs for Pompe disease. However, an increasing number of observations have been recently published showing that early pre-symptomatic treatment in CRIM-positive, low antibody titer patients does not completely prevent slow deterioration after the first years of life [ 10 , 31 , 32 ]. Moreover pre-symptomatic treatment does not always guarantee a positive outcome in a short-term, as shown by Schänzer et al [ 33 ], who reported an extreme case of a CRIM-positive, low antibody titer IOPD infant, treated since the 3rd day of life with 40 mg/kg/week who never achieved free sitting position and was tracheostomized and ventilated from 10 months on [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 However, treatment of severe cardiac disease remains quite challenging. [13][14][15] CONCLUSION Typically, patients with infantile-onset Pompe disease and severe hypertrophic cardiomyopathy are not as responsive to enzyme replacement therapy as patients with mild or no hypertrophic cardiomyopathy. Our patient had severe hypertrophic cardiomyopathy, and despite her death, we believe that her heart had significantly improved, and her death was related to the sequelae of her respiratory infection and hypotonia rather than cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, presently only brain autopsies in untreated patients have shown clear evidence of glycogen storage in the CNS [ 45 , 46 ], and periventricular white matter abnormalities on brain magnetic resonance imaging (MRI) have been seen in children receiving ERT [ 1 ]. Measuring the effects of CNS pathology on cognitive function is confounded by co-occurring hearing loss, speech muscle pathology, and fine motor dysfunction; however, it is clear from emerging signs and symptoms, which may be caused by neuronal glycogen deposition, that ERT is unable to address all aspects of the disease at least in infants with Pompe disease [ 3 , 47 51 ]. While ERT clearly slows disease progression for many patients, available data demonstrate that it is limited in its ability to improve and maintain clinical symptomatology and associated disease burden in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the burden of the disease remains high, and while the improved survival of many patients has led to a shift in the ‘natural history’ to modified disease stages and phenotypes, it has not led to a cure [ 6 , 53 ]. Indeed, it is clear that ERT is unable to address all aspects of this disease, particularly in terms of those etiologies associated with neuronal glycogen deposition [ 3 , 47 51 ]. Crucially, substantial morbidity persists, and, particularly in infants, mortality rates remain high at 28–43% [ 53 56 ].…”
Section: Discussionmentioning
confidence: 99%